Enhance Knowing Thyself and Self-Development Based on Personality Types Through LKMM Implementation - Balan, John M; Lina, Virgilius Bate; Rato, Virgilia S. Gele; Bolet, Bernadus (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Getting to know and developing oneself is a task in every stage of human life development. Knowing and developing oneself into a potential individual, various approaches and methods should be used to achieve the goals. LKMM is one of the many approaches and ways to help students recognize and develop their own self potential. What does the abbreviation LKMM stand for? The abbreviation LKMM stands for the following characteristics: L (Latihan) K (Keterampilan) M (Manajemen) M (Mahasiswa) which means Students Skill Management Training (SSMT). The aim of this journal article is to re-mix the theme of